Studies on the Effect of Different Light Intensity and CO2 Concentration Towards Chlorella sp. Growth Using Palm Oil Effluent (POME) - Yeo, Wee Kiat; Mira Sabriena, Misri; Chua, Gek Kee; Jailani, Salihon; M. M., Yusoff; Mohd Hasbi, Ab. Rahim; Natanamurugaraj, Govindan (2014)
Carbon dioxide (CO) is major gas that lead to global warming. CO sequestration by microalgae has been extensively studied recently since it is able to utilize CO2 for photosynthetic activity and has higher production rate as compared tp plant. Malaysia produced large amount of palm oil mill effluent (POME) every year and its contain high nutrient that was potentially act as medium for microalgae cultivation.